Prevalence of hearing loss and use of hearing aids among children and adolescents in Germany: a systematic review - C. Schmucker; P. Kapp; E. Motschall; J. Loehler; J. J. Meerpohl (BMC, 2019)
Abstract Background Current data suggest that approximately 466 million people (5.0%) of the world's population have disabling hearing loss, therefrom, 34 million children, impacting their quality of life. To provide estimates on the prevalence of hearing loss on a national level, we reviewed the epidemiological literature addressing hearing loss in children and adolescents living in Germany as an example for a Western country. Methods We searched Medline, Web of Science, Cochrane Library, ScienceDirect and LIVIVO to identify published data. Furthermore, we manually searched websites of relevant institutions and journals not listed in electronically and searched for ongoing studies and/or not yet published data in clinicaltrials.gov. Study selection, data extraction, and methodological assessment were carried out by two reviewers. Results In total, 11 reports provided data with sample sizes ranging from 310 up to more than 14 million children and adolescents. Prevalence data were collected by interviews (self-assessments), using pure-tone audiometry or the international classification of diseases (ICD-10) coding and ranged from 0.1 to 128 per 1000 children. Although the estimate of the prevalence of hearing loss goes down, when the threshold was raised, generating a comprehensive and coherent set of estimates proved challenging owing to clinical heterogeneity including variation in age, the study setting, the definition of hearing loss and the assessment method. Moreover, representativeness (external validity) was often impaired owing to estimates lacking currentness (i.e., referring to former West Germany) or selected (patient) data and may not be typical for a more general population. Conclusions In conclusions, this work raises public awareness of the high prevalence of hearing loss, highlights issues associated with epidemiological research and is of great importance for researcher and those who use epidemiological data to inform clinical and political decision making.